Regulation of Fatty Acid Oxidation by Twist 1 in the Metabolic Adaptation of T Helper Lymphocytes to Chronic Inflammation. Issue 10 (5th September 2019) - Hradilkova, Kristyna; Maschmeyer, Patrick; Westendorf, Kerstin; Schliemann, Heidi; Husak, Olena; von Stuckrad, Anne Sae Lim; Kallinich, Tilmann; Minden, Kirsten; Durek, Pawel; Grün, Joachim R.; Chang, Hyun‐Dong; Radbruch, Andreas
Abstract : Objective: Inflamed tissue is characterized by low availability of oxygen and nutrients. Yet CD4+ T helper lymphocytes persist over time in such tissue and probably contribute to the chronicity of inflammation. This study was undertaken to analyze the metabolic adaptation of these cells to the inflamed environment. Methods: Synovial and blood CD4+ T cells isolated ex vivo from patients with juvenile idiopathic arthritis (JIA) and murine CD4+ T cells were either stimulated once or stimulated repeatedly. Their dependency on particular metabolic pathways for survival was then analyzed using pharmacologic inhibitors. The role of the transcription factor Twist 1 was investigated by determining lactate production and oxygen consumption in Twist1 ‐sufficient and Twist1 ‐deficient murine T cells. The dependency of these murine cells on particular metabolic pathways was analyzed using pharmacologic inhibitors. Results: Programmed death 1 (PD‐1)+ T helper cells in synovial fluid samples from patients with JIA survived via fatty acid oxidation (mean ± SEM survival of 3.4 ± 2.85% in the presence of etomoxir versus 60 ± 7.08% in the absence of etomoxir on day 4 of culture) ( P < 0.0002; n = 6) and expressed the E‐box–binding transcription factor TWIST1 (2–14‐fold increased expression) ( P = 0.0156 versus PD‐1− T helper cells; n = 6). Repeatedly restimulated murine T helper cells, which expressed Twist1 as well, needed Twist1 to survive via fatty acid oxidation. In addition, Twist1 protected the cells against reactive oxygen species. Conclusion: Our findings indicate that TWIST1 is a master regulator of metabolic adaptation of T helper cells to chronic inflammation and a target for their selective therapeutic elimination.